Scientific Investigation of Laws of Kazakhstan for Compliance with National Interests - MAMONOV, Vassiliy; SALIMGEREY, Aron; BAZAROV, Yerdan; NURTILEU, Maigul (Journal of Advanced Research in Law and Economics; Vol 10 No 5 (2019): JARLE Volume X Issue 5(43) Fall 2019, 2019)
The laws regulate the most important social relations. Their quality and effectiveness directly determine condition of key national interests protection. Taking into account these organic interconnections, the Law of Kazakhstan ‘On National Security of Kazakhstan’ contains the rule that the requirements for ensuring national security are necessarily taken into account when developing, accepting and executing legislative and other normative legal acts in the field of national security. When considering scientific investigation as the main tool of security support of the legal regulation, it has been established that existing types of expertise in Kazakhstan cannot fully ensure implementation of these legislative requirements. The result of research is justification for the need to introduce scientific investigation to follow national interests as an independent type of investigation under individual laws at all stages of their ‘life cycle’ – development, acceptance, execution. At the same time, provisions are being put forward on further directions of development of this institution in Kazakhstan.